Dietary intake and lifestyle practices of eastern mediterranean postpartum women before and during COVID-19 pandemic: An internet-based cross-sectional survey - Tayyem, Reema; Al-Bayyari, Nahla; Al-Awwad, Narmeen; Abuhijleh, Haya; Hoteit, Reem; Qasrawi, Radwan; Badran, Eman; Basha, Asma; Allehdan, Sabika; Boukari, Khlood; Arrish, Jamila; Seir, Rania Abu; et al. (Frontiers in Nutrition, 2022)
Background: During the lockdown period, a substantial group of these women reported lifestyle changes. Aim: The aim of the study is to characterize the dietary patterns, intake and the adherence to the United States Department of Agriculture (USDA) pregnancy guidelines before and during the COVID-19 pandemic in Eastern Mediterranean postartum women. Methods: An internet-based cross-sectional survey was used to collect the data. The survey was carried out among 1,939 postpartum women from five countries from the Eastern Mediterranean region. Change in dietary intake from the five food groups and the adherence to USDA's daily recommendations were assessed. Findings: There was a significant increase in the mean (±SD) consumption of all the food groups, including bread, rice, and other cereals, fruits, vegetables, milk and milk products, white and red meat, and nuts during the pandemic. Around 84% of participants reported no/low adherence (0-2) to USDA guidelines, whereas only 15% reported moderate or high adherence (3-5) to the guidelines before the pandemic. However, there was an increase in the proportion of subjects reporting moderate/high adherence (22%) during the pandemic. Discussion and Conclusions: A substantial proportion of our study participants reported a lower dietary intake than the recommended amounts and low adherence to the five food groups. Reasonable and applicable actions should be taken to protect postpartum women and their children from the effects of low dietary intake, particularly during pandemics and lockdowns. More researches are needed to identify the modifiable factors which could improve the nutritional status of the postpartum women during the pandemic.